Kebijakan Tax Amnesty Dalam Rangka Mewujudkan Kesadaran dan Kepatuhan Wajib Pajak Di Provinsi Bali - Made Nidya Lestari Karma; Ni Putu Nina Eka Lestari (Jurnal Manajemen dan Bisnis, 2018)
ABSTRACTIndonesia is a developing country, on the course there are often changes in regulations / legislation (deregulation) with regard to all fields (Supriyadinata et al., 2016).  To increase tax revenues and to raise awareness and compliance of Taxpayers in Indonesia, from 1st July 2016 to 31st March 2017 a program called Tax Amnesty has been implemented. The implementation of Tax Amnesty is marked with the issuance of Tax Amnesty Act and the Regulation of the Minister of Finance concerning the Transfer of Taxpayers' property from abroad into the country.The purpose of this research is to determine and analyze the influence of Taxpayer's knowledge about Tax Amnesty, Implementation of Tax Amnesty and Policy of transfer of property in the framework of Tax Amnesty to the awareness of Taxpayer and compliance of Taxpayer in Bali Province. Data were obtained from 160 respondents listed as taxpayers at Denpasar Barat Tax Office. The design of this research is quantitative research that explains the causal relationship of each variable. To answer the hypothesis proposed in this study, the data were analyzed using structural ecquation modeling with AMOS program. The results of this research showed that Taxpayer's knowledge about Tax Amnesty, Implementation of Tax Amnesty and Policy of transfer of property in the framework of Tax Amnesty  have positive influence on taxpayer awareness and taxpayer compliance and taxpayer awareness have positive and significant impact on tax compliance too.